(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
It has been the policy and practice norm for government of Malaysia since independent day to own all utility facities like water, gas, electricity, sewage and telecommunication. In line with international practice and standard, it is preferable for utility providers, installers and contractors whenever possible to install their utility cables and pipes underground. Unfortunetaly until now the so called underground utility policy remains unwritten. Malaysia has instead enacted and use several laws to fulfil the policy gaps. The Street, Drainage and Building Act 1974 (Act 133) is the first general law enacted for utility facilities and followed by other specific Acts which govern other utility facilities like electricity, telecommunications and water supply. All utility agencies providers or installer must adhere to the stipulated requirements of section 40(1)of Act 133 in installing utilities facilities underground. The second limb of the same provision gives the government the legislative power to impose conditions as it deems legally necessary within the law on projects involving utility facilities. Such approach seems to work for quite sometime. However as the nation progresses and the demands of mapping works becomes more complicated, loopholes begining to appear in the provisions of Act 133 regarding utility facilities. The Acts is silent on the requirement to survey and map the precise locality and depth of the installed underground utility facilities. JUPEM has issued rules, guidelines and standard operation procedures in overcoming the legal inadequacies. Although the crafted soft laws are necessary in facilitating the implementation of policies, they do not enjoy the same legislative status or authority as the hard laws. This paper highlights the role of hard and soft laws as policy instruments and discusses the challenges faced by JUPEM on mapping of underground utility in absence of a written policy towards meeting and achieving the international standard.